Management of a Neisseria meningitidis case: factors that guarantee the effectiveness of supporting Public Health actions - Voltolini, Anna; Marcotrigiano, Vincenzo; Cian, Serena; Fiorito, Nahuel; Sollano, Alfonsina; Dall'O, Ilaria; Baldo, Vincenzo; Cinquetti, Sandro (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Among invasive bacterial diseases, meningococcal meningitis is a serious and contagious disease caused by Neisseria meningitidis. The disease has a high lethality grade and could have long-term sequelae. This paper describes a case of meningitis that occurred in the territory under the jurisdiction of Local Health Authority ULSS 1 Dolomiti and the related management methods. The activities described concern rapid alerts, an epidemiological investigation, the administration of chemoprophylaxis and offering vaccinations, implemented according to the current Public Health protocol through different healthcare workers. This case report aims to support the management of possible similar cases, underlining the conditions that favoured the application of the envisaged measures, including an on-call ready availability service; the presence of population vaccination centres located in the area investigated; and a network sensitive to early warnings and collaboration within and between Local Health Authorities.